THE ISLAMIC RELIGIOUS GUIDANCE AND MORAL TRANSFORMATION: A STUDY OF PRISON REHABILITATION IN NORTH SUMATERA - Basuki, Listari; Nahar, Syamsu; Arsyad, Junaidi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Religious guidance in prisoners can aid rehabilitation, especially in Muslim-majority nations like Indonesia. Purpose: However, these programs' objectives and effectiveness, especially in moral change and social reintegration, have rarely been evaluated. Method: This multisite qualitative case study uses in-depth interviews, document analysis, and field observations to analyze the goals and implementation of Islamic religious guidance for convicts in Labuhan Ruku, Tebing Tinggi, and Tanjung Balai prisons in North Sumatra. Result: The study found that Islamic religious guidance can help convicts repent, discipline, and self-aware and prepare for reintegration. Prisoners reported less violence and a more positive identity. Trained religious counselors, institutional support, and planned follow-up following release are crucial to this transformation's persistence. Religion-based rehabilitation without coordinated reintegration programs may be temporary due to a lack of external support after incarceration. These findings show that Islamic religious instruction can be used as a spiritual tool and a rehabilitation method when supported by cross-sectoral initiatives. Conclusion: Therefore, to institutionalize spiritual growth in Indonesia's holistic correctional reform, religious leaders, correctional authorities, and policymakers must collaborate.